2014
DOI: 10.3389/fnbeh.2014.00127
|View full text |Cite
|
Sign up to set email alerts
|

Corticosterone and decision-making in male Wistar rats: the effect of corticosterone application in the infralimbic and orbitofrontal cortex

Abstract: Corticosteroid hormones, released after stress, are known to influence neuronal activity and produce a wide range of effects upon the brain. They affect cognitive tasks including decision-making. Recently it was shown that systemic injections of corticosterone (CORT) disrupt reward-based decision-making in rats when tested in a rat model of the Iowa Gambling Task (rIGT), i.e., rats do not learn across trial blocks to avoid the long-term disadvantageous option. This effect was associated with a change in neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 77 publications
(138 reference statements)
0
13
0
Order By: Relevance
“…Chronic high-dose systemic injections of corticosterone were shown to cause significant reduction of spines in PFC pyramidal neurons of layer V and deficits in memory retention ( 67 ), and to induce a significant redistribution of apical dendrites in layers II/III, with an increase in the number of proximal dendrites and a reduction of distal dendrites ( 68 ). Repeated corticosterone injections within infralimbic and prelimbic medial PFC were also found to impair working memory and to improve memory consolidation, through a glucocorticoid receptor-dependent mechanism ( 69 ). On the other hand, repeated corticotropin-releasing factor infusion directly into the medial PFC increased general anxiety, but did not affect cue-conditioned fear 10 days post infusion ( 70 ).…”
Section: Glutamatergic and Morphological Dysfunctions In Cortical Arementioning
confidence: 99%
“…Chronic high-dose systemic injections of corticosterone were shown to cause significant reduction of spines in PFC pyramidal neurons of layer V and deficits in memory retention ( 67 ), and to induce a significant redistribution of apical dendrites in layers II/III, with an increase in the number of proximal dendrites and a reduction of distal dendrites ( 68 ). Repeated corticosterone injections within infralimbic and prelimbic medial PFC were also found to impair working memory and to improve memory consolidation, through a glucocorticoid receptor-dependent mechanism ( 69 ). On the other hand, repeated corticotropin-releasing factor infusion directly into the medial PFC increased general anxiety, but did not affect cue-conditioned fear 10 days post infusion ( 70 ).…”
Section: Glutamatergic and Morphological Dysfunctions In Cortical Arementioning
confidence: 99%
“…Unimpaired IGT performance has associated with intact function of the OFC [ 17 , 18 , 19 ]. Even in a rat analogue of the IGT, rats with OFC lesions preferred to choose larger but more unpredictable rewards over smaller but more reliable rewards under conditions of uncertainty and ambiguity [ 20 , 21 ] or showed inadapted behaviors and impaired performance [ 22 , 23 ]. However, previous studies have suggested that the dlPFC plays a major role in the GDT.…”
Section: Introductionmentioning
confidence: 99%
“…A number of new tasks for rats have been developed to study choice between options that vary in terms of economic costs and benefits. These include the rat Gambling Task (rGT; van den Bos et al, 2006 , 2012 , 2013 , 2014 ; Rivalan et al, 2009 , 2013 ; Zeeb et al, 2009 ; Zeeb and Winstanley, 2011 , 2013 ; Koot et al, 2012 , 2013 , 2014 ) and the probabilistic delivery task (PDT; Adriani and Laviola, 2006 ; Adriani et al, 2006 , 2009 , 2010 ; Koot et al, 2012 ; Zoratto et al, 2013 , 2014 ). On these tasks, contingencies are arranged so that choice of the large reward option(s) is economically suboptimal.…”
Section: Introductionmentioning
confidence: 99%